2017
DOI: 10.1186/s13075-017-1437-3
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles from patients with systemic lupus erythematosus induce production of reactive oxygen species and degranulation of polymorphonuclear leukocytes

Abstract: BackgroundThe interaction of circulating microparticles (MPs) with immune cells in systemic lupus erythematosus (SLE) is sparsely investigated. We examined the ability of MPs from SLE patients to induce production of reactive oxygen species (ROS) and degranulation of polymorphonuclear leukocytes (PMNs).MethodsPlasma MPs, leukocytes and sera isolated from 20 SLE patients and 10 healthy controls were mixed in different combinations, with or without lipopolysaccharide (LPS), and incubated for 30 min. Dihydrorhoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Similar results have been reported for MVs derived from cells subjected to stress or under pathological conditions. MVs derived from ischemic muscles (56), plasma of patients with lupus [99] or neutrophils infected with Mycobacterium tuberculosis [70] were shown to induce ROS in mononuclear cells, neutrophils and macrophages, respectively. However, MVs derived from cells exposed to ROS induced ROS tolerance in PC12 cells [100].…”
Section: Microvesicles and Rosmentioning
confidence: 99%
“…Similar results have been reported for MVs derived from cells subjected to stress or under pathological conditions. MVs derived from ischemic muscles (56), plasma of patients with lupus [99] or neutrophils infected with Mycobacterium tuberculosis [70] were shown to induce ROS in mononuclear cells, neutrophils and macrophages, respectively. However, MVs derived from cells exposed to ROS induced ROS tolerance in PC12 cells [100].…”
Section: Microvesicles and Rosmentioning
confidence: 99%
“…Moreover, it was shown that these increased EVs in the plasma of active SLE patients induced ROS production and degranulation in neutrophils 187 , activated pDCs to secrete IFN-α via TLR7 188 , or contributed to MSC senescence in SLE 189 . The elevated EVs and their immune complexes in SLE patients also promoted secondary leukocyte infiltration by regulating vascular remodeling and chemokine secretion 16 .…”
Section: Ev Involvement In the Pathophysiology Of Inflammatory Skin Dmentioning
confidence: 99%
“…Dieker et al reported that circulating apoptotic MPs from SLE patients drive the activation of dendritic cell subsets and prime neutrophils [ 74 ]. In another study, Winber et al demonstrated that SLE patients display increased ROS production and degranulation by polymorphonuclear leukocytes (PMNs) in response to MPs [ 75 ]. Recently, Burbano et al highlighted the involvement of platelet-derived MPs during monocyte activation in patients with SLE, showing that MPs are one of the most representative sources of the total amount of circulating ICs-IgG + in patients with SLE [ 76 ].…”
Section: Role Of Extracellular Vesicles In Systemic Lupus Erythemamentioning
confidence: 99%